Evaluating the success of the tele-pathology system in governmental hospitals in Kuwait: an explanatory sequential mixed methods design - Buabbas, Ali Jasem; Mohammad, Tareq; Ayed, Adel K.; Mallah, Hawraa; Al-Shawaf, Hamza; Khalfan, Abdulwahed Mohammed (BMC medical informatics and decision making, 2021)
Background Telepathology is the practice of reviewing and exchanging pathological images through telecommunication systems to obtain diagnoses remotely. Studying the factors that make such a system successful and favourable is important to ensure the merits of its implementation in clinical practice. Objective This study aims to evaluate the success of a telepathology system from the users’ perspectives, using specific evaluation criteria, namely: system quality, information quality, technical service quality, user satisfaction, and benefits. Methods A sequential explanatory mixed methods design was adopted in this study, which consists of two phases. Initially, a questionnaire was distributed via WhatsApp to all of the pathologists (total: 45) working at governmental hospitals in Kuwait. Followed by, semi-structured interviews with ten senior pathologists. Results Forty pathologists responded to the questionnaire, giving an 89% response rate. There were 42.5% of the respondents aged between 35–44 years old, and 52.5% were male. The quantitative results reveal that most of the respondents were satisfied with the quality of the telepathology system with a mean of 2.6025 (Standard Deviation (SD) = 0.47176), whereas they were dissatisfied with the quality of the information with a mean of 2.4100 (SD = 1.580) and the technical support services with a mean of 2.2750 (SD = 0.99535). In addition, there was disagreement on the benefits of telepathology in clinical practice among the pathologists with a mean of 2.4667 (SD = 0.77552). The qualitative results indicate that the lack of interest in and little experience with using the system were behind the general dissatisfaction of most of the respondents. All of the interviewees were satisfied with the performance of the telepathology system and considered it successful; however, the quality of the technical support services, including training workshops, was deemed deficient. Conclusion This study concluded that telepathology system in Kuwait is functioning well and has been successful in its implementation; however, pathologists are dissatisfied with it, mainly due to the deficient quality of the technical support services provided. In addition, the successful implementation of such advanced technologies requires careful steps to be taken on multiple levels: technical, organisational, and managerial. Recommendations were suggested.